2017
DOI: 10.14748/ssmd.v3i1.2958
|View full text |Cite
|
Sign up to set email alerts
|

Bone characteristics and implant stability

Abstract: The aim of this literature data review was to investigate the influence of the bone density, bone volume, cortical bone thickness and the anatomical area on the primary stability of dental implants. Understanding the effect of the bone quality could help us predict the primary stability and prevent to some extent the poor implant stability by choosing implants of different design, diameter, length or surface modification.Considering the reviewed articles, we have concluded that inserting implants in dense bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Successful dental implant treatment relies on both the quality and quantity of the available alveolar bone. [ 31 ]. The term ''bone quality'' has not been clearly defined in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Successful dental implant treatment relies on both the quality and quantity of the available alveolar bone. [ 31 ]. The term ''bone quality'' has not been clearly defined in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Leckholm and Zarb classification [15], a type A-2 mandibular section was created, which consisted of a layer of compact cortical bone surrounding a core of dense trabecular bone. This type of bone is the most common for this mandibular region as reported in the literature [13,[16][17][18]. The dimensions of the bone section were 23 mm high and 12 mm wide.…”
Section: Bonementioning
confidence: 82%
“…Previous studies have investigated the relationship between bone density and primary implant stability and have revealed variable correlations. [32][33][34] In a clinical study by Turkyilmaz et al 34 a strong correlation between bone density and ISQ values was found. Herekar et al 35 proposed a scoring index according to which the primary stability was 77.35 in D2 bone, 70.55 in D3 bone, and 60 in D4 bone.…”
Section: Discussionmentioning
confidence: 99%